COMBINING INTERACTIVE VOCABULARY AND GAME: IS IT A WAY TO BOOST CHINESE LEARNERS' BIPA SKILLS? - Ni Wayan Krismayani; Putu Nur Ayomi; I Komang Budiarta (Jurnal Santiaji Pendidikan (JSP), 2025)
This research aims at finding out the implementation of the students’ vocabulary combined with game activity in BIPA class. Research respondents for this study were 10 international students from China who enrolled in Bahasa Indonesia bagi Penutur Asing (BIPA) at Universitas Mahasaraswati Denpasar. This research used a phenomenological method with a qualitative design. The findings indicated that the use of interactive vocabulary combined with game are effective to be applied in BIPA Class. However, BIPA students also encountered several challenges in pronouncing word in Indonesian. Therefore, to boost their language skill, the researcher proposed interactive vocabulary combined with games.